Дело было в Пенькове: повести / Сергей Антонов - Антонов Сергей Петрович (Сделано в СССР, 2011)
Экземпляры: Ф. 13 (20191017) / Инвентарный номер: 43139 / Цена: 183.38 / Сис.шифр: Р2 / Авт.знак: А 72 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6